COVID-19 and nutrition state-level monitoring report for India - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The report was posted online in 2020 and builds on the work and partnerships of a multi-year initative led by IFPRI called POSHAN (Partnerships and Opportunities to Strengthen and Harmonize Actions for Nutrition in India). The report is compiled by POSHAN with multiple other partners.